Pharmacotherapy for Non-alcoholic Fatty Liver Disease - Gawrieh, Samer (Semin Liver Dis, 2015)
Life style modifications and optimization of the management of cardio-metabolic comorbidities are currently the mainstay of treatment for patients with non-alcoholic fatty liver disease (NAFLD). Pharmacotherapy to halt or reverse hepatic histological injury and prevent the development of end stage liver disease is specifically offered to patients with non-alcoholic steatohepatitis (NASH) and those with advanced fibrosis. In this review, we will discuss state of the art of various pharmacological agents for NASH. The efficacy of vitamin E and pioglitazone is reasonably well established in a select group of patients with NASH. Current data do not offer convincing evidence for efficacy of pentoxifylline, long-chain polyunsaturated fatty acids, angiotensin receptor blockers, metformin or ursodeoxycholic acid. We also discuss the state of several emerging agents for treating NASH including the farsenoid X receptor (FXR) ligand, obeticholic acid.